Introduction to Post-Tonal Theory - Straus, Joseph N. (Hoboken, NJ Prentice Hall, 2004)
Designed for a course in twenty-first-century techniques and analysis, this text offers a clear, comprehensive introduction to the basic concepts of post-tonal theory. Each concept is clearly explained and richly illustrated with examples from the musical literature. The text contains model analyses as well as carefully graduated exercises that involve playing, singing, composing, and analyzing. The third edition stays abreast of recent theoretical developments by including discussions of transformational networks and graphs, contour theory, atonal voice leading, triadic post-tonality (including neotonality), inversional symmetry, and interval cycles. As a result, this text is not only a primer of basic concepts but also an introduction to the current state of post-tonal theory, with its rich array of theoretical concepts and analytical tools. The third edition also features a wide range of composers and musical styles. Although the "classical" prewar repertoire of music by Schoenberg, Stravinsky, Bartok, Webern, and Berg still comprises the musical core, theoretical concepts are now also illustrated with music by Adams, Babbitt, Berio, Boulez, Britten, Cage, Carter, Cowell, Crawford, Crumb, Debussy, Feldman, Glass, Gubaidulina, Ives, Ligeti, Messiaen, Musgrave, Reich, Ruggles, Sessions, Shostakovich, Stockhausen, Varese, Wolpe, Wuorinen, and Zwillich.
Keywords: 21st Century (2001-2100); Music theory; Musical analysis